Karakteristik Perpindahan Panas Dan Penurunan Tekanan Pin Fin Cooling Susunan Segaris Segaris Pada Trailing Edges Sudu Turbin Gas - FAISHAL, ADNAN ARIF (2016)
ABSTRACT This CFD study presents the performance evaluation of a blade cooling passage. An experimental model with seven-row of inline circular pin-fins is chosen in this study. Simulations consider two types; i.e. 'warm' test with isothermal wall condition and 'cold' test with adiabatic wall condition respectively, in order to evaluate flow and thermal characteristics such as heat transfer coefficient (HTC) and friction factor (f). The steady RANS with k-epsilon turbulence model was carried out by two-stages investigating: firstly, validation of an existing circular staggered array of pin-fin cooling that has been experimentally studied by other researcher. Three types structured mesh from coarse (Δy+ = 11.83) to fine (Δy+ = 1.23) were applied for validation. Secondly, further investigation of the circular pin-fin cooling with in-line array was simulated by adopting the same scenario of mesh generation based on the optimum result from validation stage. Simulations were performed by keeping the same initials and boundary conditions as experiment, and varying Reynolds number between 9.000 and 36.000. The result indicates that the CFD predicted data can be considered acceptable by generating mesh up to 1.6 million elements with fine resolution (Δy+ = 1.23). The CFD predicted HTC and pressure loss are in good agreement with available experimental data, though over-prediction data is clearly seen after the second pin-fin row for warm simulation. By comparing the pin-fin array between "staggered" and "in-line", it was found that the HTC of staggered array is higher than the in-line orientation. It is due to the staggered layout causes to intensify the coolant flow around the pin-fin. The HTC of pin-fins surface increases moderately along the cooling passage due to the increase of flow turbulence that caused by contraction channel and increasing Reynolds number. Whilst, the friction factor decreases gradually along the cooling passage. Key words : Pin-fin cooling; Computational fluid dynamics; Heattransfer coefficient